Interactive DTI-Based Constrained Tractography using OpenGL Pipeline - Shin-Ting, Wu; Voltoline, Raphael; Benites, Rodrigo L. (Anais da Conference on Graphics, Patterns and Images (SIBGRAPI); 2023: Anais da XXXVI Conference on Graphics, Patterns and Images, 2023)
This paper addresses the limitations of the DTI-based tracking algorithms commonly applied in routine clinical practice. Interactive tracking and rendering algorithms are presented using the OpenGL pipeline, allowing experts to explore, adjust, interpret, and validate the reconstructed pathways. The key features of our algorithms are fiber tracking preprocessing and separation of tracking and rendering stages.